Produksi Bahan Kering dan Kadar Nutrien Indigofera zollingeriana di Lahan Gambut Berdasarkan Umur Panen Berbeda Setelah Pemangkasan: Dry Matter Production and Nutrient Content of Indigofera zollingeriana on Peatland Area Based on Different Harvesting Age after Trimming (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2021)
This study aimed to determine the increase of dry matter production and Nutrient changes of Indigofera zollingeriana  cultivated in Sapric peat soils with harvest age of  2, 3 and 4 months after pruning. Indigofera foliage was obtained from the existing plot of approximately 3 years old  that grown in the experimental field of the UARDS Laboratory of the Faculty of Agriculture and Animal Sciences of UIN Suska Riau. The research design of  randomized block design (RBD) was apllied consisting of 3 age treatments with 4 group. Each treatment, consisted of indigofera biomass harvested at 2 months old (2M),  3 months old (3M) and  4 months old (4M). The results showed that postponing harvest from 2 months to 4 months significantly (p